Studi Literatur Penerapan Teori Graf Dalam Rekomendasi Teman di Media Sosial - Muhammad Raffa Abdillah; Athia Saelan; Ismail Ismail (Universitas Indonesia Membangun (Inaba), 2026)
Social media is a platform for a vast network of friends. Friendship networks on social media are usually represented in the form of graphs. One of the main features of social media is friend recommendations. This research is a literature study on methods that can be used to provide friend recommendations on social media. To provide accurate friend recommendations on social media, certain methods derived from graph theory are required. Some of the methods discussed include centrality, similarity, trust value, and community detection. Based on the literature study, the steps for building a friend recommendation system include data collection, graph construction, graph structure analysis, application of similarity and trust value, and system evaluation. With these methods, it is hoped that the recommended friends will be more accurate and suit the user needs.